2010
DOI: 10.4314/fje.v2i1.50790
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of urban heat island of Lokoja Town and surroundings using LandSat ETM data.

Abstract: The urban centre and its suburban environment are largely influenced by changes driven by people as a result of urbanization and other anthropogenic activities. Urbanization impacts on air and water quality, local climate and biodiversity. This study assesses the Urban Heat Island (UHI) of Lokoja town and surroundings from LandSat ETM satellite imagery of 2001 using remote sensing techniques. Band 3, 4 and 6 of the imagery were use in the estimation of NDVI, land surface emissivity and surface temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
0
1
Order By: Relevance
“…The analysis showed a variability of +5.32 o C and +1.03 o C maximum and minimum temperature in the Nguru between 2001 and 2021 respectively, as shown in Table 6. The difference was found not to be sizeable in comparison to the studies by Ifatimehin (2007) and Qiquan and Jiayi (2017).…”
Section: Land Surface Temperature (Lst) Response To Changes In Land C...contrasting
confidence: 81%
See 1 more Smart Citation
“…The analysis showed a variability of +5.32 o C and +1.03 o C maximum and minimum temperature in the Nguru between 2001 and 2021 respectively, as shown in Table 6. The difference was found not to be sizeable in comparison to the studies by Ifatimehin (2007) and Qiquan and Jiayi (2017).…”
Section: Land Surface Temperature (Lst) Response To Changes In Land C...contrasting
confidence: 81%
“…Variations in minimum and maximum temperatures are alleged to have occurred within Nguru as a result of a massive drop in vegetative cover and an upsurge in built-up areas. The LST research findings are consistent with those ofIfatimehin (2007) who observed that Surface Urban Heat Island (SUHI) is higher in the city center and decreases as one moves outward, as well as the research findings of(Aslan and Koc-San, 2016;Khaled, et al, 2015; Zaharadeen et al, 2016).…”
supporting
confidence: 87%